Empowering Local MSMEs through Branding, Product Design, and Digital Marketing: A Community Engagement Program at Pringgondani Market, Balikpapan - Mega Silfiani; Irma Fitria; Hairul Irawan; Rianto Padli; Dewi Leonita Sari; Nur Annisa; Nadya Alivia Raaph; Kayla Salbina Zahra; M. Daffa Rivaldy Darwis; Sunrie Kristella Lastiur; Michell Patricia (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to strengthen the capacity of micro, small, and medium enterprises (MSMEs) in branding, product design, and digital marketing in order to enhance their business competitiveness. The program was implemented through a series of training sessions and mentoring activities involving 57 MSME participants. It consisted of three main components: (1) branding and business preparation, (2) product and packaging design using simple digital tools, and (3) social media–based marketing for digital promotion. Evaluation was conducted using pre- and post-training tests, structured questionnaires, and visual documentation of product packaging. The data were analyzed using descriptive statistics and comparative analyses of participants’ test scores and design outputs. The results indicate substantial improvements in participants’ understanding of branding principles, design aesthetics, and digital literacy. Quantitatively, the average test score increased from 9.1 in the pre-test to 10.0 in the post-test, and many participants successfully redesigned their product packaging and began using social media more systematically for promotional purposes. As a result, MSME owners developed clearer product identities, more attractive packaging, and more consistent online engagement. Overall, the program demonstrates that short-term, community-based interventions can effectively enhance MSME competitiveness and digital readiness while supporting sustainable local economic growth. These findings underscore the importance of integrating creativity, technology, and community participation in MSME empowerment initiatives.